The pore water pressure changes on forested slopes in tropical humid climate area - Hendrayanto; Yulia Amirul Fata; Muhamad Askari; Erizal; Suria Darma Tarigan; Ery Suhartanto (ResearchGate, 2024)
This study investigates the pore water pressure and water content on a forested slope, focusing on the impact of canopy interception across various rainfall intensities. The study was performed on slopes in the Sukajaya Sub District of West Bogor, West Java, Indonesia, a region that encountered landslides in 2020. Soil hydraulic characteristics, soil textures, saturated water content, and soil moisture content at different pressures, were assessed at different slope locations and depths. The pore water pressure and water content change were simulated using the one-dimensional uniform (equilibrium) finite element model of water movement using the modified Richards and were executed with the HYDRUS 1D model across six scenarios of a combination of three rainfall events at two initial conditions of water content, contrasting bare and vegetated slopes of Maesopsis eminii, which exhibited 35% canopy interception. Findings demonstrate that bare soil attains saturation more rapidly, resulting in elevated pore water pressure and increased susceptibility to slope instability. Conversely, vegetated slopes have delayed saturation owing to canopy interception, which diminishes the volume of rainfall that reaches the soil. The results highlight the crucial function of vegetation in preserving slope stability by regulating soil water pressure and water content, particularly during intense rainfall events. This research enhances comprehension of how vegetated areas might reduce landslide hazards in high-rainfall environments.